A 1,000-year-old antimicrobial remedy with anti-Staphylococcal activity - Harrison, Freya; Roberts, Aled; Gabrilska, Rebecca; Rumbaugh, Kendra; Lee, Christina; Diggle, Stephen P. (American Society for Microbiology, 2015)
Plant-derived compounds and other natural substances are a rich potential source of compounds that kill or attenuate pathogens that are resistant to current antibiotics. Medieval so- cieties used a range of these natural substances to treat conditions clearly recognizable to the modern eye as microbial infections, and there has been much debate over the likely efficacy of these treatments. Our interdisciplinary team, comprising researchers from both sciences and hu- manities, identified and reconstructed a potential remedy for Staphylococcus aureus infection from a 10th Century Anglo-Saxon Leechbook. The remedy repeatedly killed established S. aure- us biofilms in an in vitro model of soft tissue infection and killed methicillin-resistance S. aureus (MRSA) in a mouse chronic wound model. While the remedy contained several ingredients that are individually known to have some antibacterial activity, full efficacy required the combined action of several ingredients, highlighting the scholarship of pre-modern doctors and the poten- tial of ancient texts as a source of new antimicrobial agents.